2003
DOI: 10.1002/pssc.200303858
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopy of high k thin layer by multiple internal reflection and attenuated total reflection

Abstract: A complete analysis of HfO 2 high k thin layers deposited by metal organic chemical vapour deposition (MOCVD) is made by infrared spectroscopy using different optical configurations. Multiple internal reflection (MIR) and attenuated total reflection (ATR) are used, giving information about morphology and composition of the layers. Samples under investigation are HfO 2 layer of 3 to 12 nm thick deposited at 400 and 550°C on thin silicon oxide. MIR technique elucidates carbon content in the layer and ATR informs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
17
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 15 publications
(18 reference statements)
7
17
0
Order By: Relevance
“…The crystalline films exhibit the characteristic doublet for the monoclinic structure, with peaks centered around 690 cm -1 and 770 cm -1 . These positions are in good agreement with those reported by Rochat et al [18] for HfO 2 films grown by the same technique (with tetra(diethylamino)hafnium as precursor). The peak located at 770 cm -1 is specific to the monoclinic structure as it disappears when the orthorhombic or other metastable structures are stabilized.…”
Section: Microstructure Of Hfo 2 Filmssupporting
confidence: 92%
“…The crystalline films exhibit the characteristic doublet for the monoclinic structure, with peaks centered around 690 cm -1 and 770 cm -1 . These positions are in good agreement with those reported by Rochat et al [18] for HfO 2 films grown by the same technique (with tetra(diethylamino)hafnium as precursor). The peak located at 770 cm -1 is specific to the monoclinic structure as it disappears when the orthorhombic or other metastable structures are stabilized.…”
Section: Microstructure Of Hfo 2 Filmssupporting
confidence: 92%
“…1 (a) splits into two separate ones after the NH3 anneal. These peaks are attributed to a change of the crystalline state [8], starting from an amorphous state after deposition and crystallizing with the high temperature anneal under NH3. Finally the spectra of Hf-rich alloys also show an emerging peak around 1100 cm"^ attributed to the Si-N bond indicating that nitrogen is presumably not incorporated into these alloys but is directly bonded to the silicon.…”
Section: Resultsmentioning
confidence: 99%
“…Theory predicts this doublet to be situated at 780/694 cm À1 and 683/634 cm À1 [4], and it has been ascribed experimentally to peaks at 760 cm À1 [7] or 752 and 635 cm À1 [16,22,23]. Based on the presence of this vibration around 780 cm À1 in the spectra of HfO 2 films of all thicknesses studied, it can be concluded that all of these films contain monoclinic HfO 2 .…”
mentioning
confidence: 84%
“…Normal transmission measurements are insufficiently sensitive, but the surface sensitivity can be greatly enhanced in attenuated total reflectance (ATR) [14]. The sensitivity enhancement depends on the angle of incidence, the thickness of the air gap and the dielectric constants of the ATR crystal and the film's substrate [15,16]. Here, we apply grazing angle attenuated total reflectance Fourier transform infrared (GATR-FTIR) to several high-k films of recent interest, Hf, Dy and Sc oxides, which were deposited by atomic vapour deposition (AVD) or atomic layer deposition (ALD) for high quality film growth with atomic precision.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation